South African dyslipidaemia guideline consensus statement - Klug, EQ; Raal, FJ; Marais, AD; Taskinen, M-R; Dalby, AJ; Schamroth, C; Rapeport, N; Jankelow, D; Blom, DJ; Catsicas, R; et al. (SA Heart Journal, 2017)
The European Society of Cardiology together with the European Atherosclerosis Society published updated dyslipidaemia guidelines in 2011. SA Heart and the Lipid and Atherosclerosis Society of Southern Africa officially adopt these guidelines. This statement adapts aspects of the guidelines to the South African situation. Using the updated Framingham risk charts, interventional strategies are based according to the cardiovascular risk score and low-density lipoprotein cholesterol (LDL-C) levels. The Framingham risk score refers to the 10-year risk of any cardiovascular event, and includes four categories of risk. Treatment targets are those of the European guidelines. The LDL-C goal is 1.8mmol/l for the very high-risk group (>30%), 2.5mmol/l for the high-risk group (15 - 30%), and 3mmol/l for those below 15% risk. Intensive management of dyslipidaemia in South Africa will significantly reduce the cardiovascular disease health burden.